Implementation of the Inclusion Program in the Performing Arts Class at XYZ School in Jakarta - Vimala Murti Pitra Tunggal Jaya (research, training and philanthropy institution Natural Aceh, 2023)
Every learner matters equally despite all learning needs, and to achieve this, the implementation of inclusion is important, especially in teaching and learning. Inclusion means providing opportunities for all students with unique learning needs to learn with other students in a general educational environment. Successful inclusive education acknowledges, comprehends, and addresses student variety and variances. This present study aimed to know the implementation of inclusion programs in the Performing Arts class at XYZ School. The study involved eight Arts teachers. The research used a research design to obtain data or information through teachers’ questionnaires and open-ended questions through interviews about inclusion programs, especially in Performing Arts education. The questions were designed in a Likert Scale format. The finding showed that most teachers understand the importance of inclusion programs in teaching and learning. The result showed that 2 (25 %) teachers strongly agreed and 6 (75%) teachers agreed that the inclusion program is important to be implemented in the school. Some strategies and challenges were also shared during the interview. Hence, to complete this challenging task, teachers, parents, and schools need to collaborate to achieve common objectives. Furthermore, facilities, professional development, training, and collaboration are essential to support inclusion. The study's findings, teachers, believe that inclusion programs are important, and to complete this challenging task, teachers, parents, and schools need to collaborate to achieve common objectives